CHEMICAL COMPOSITION OF SPRING DISCHARGE IN THE AREA OF MINING WASTE STORAGE AND POTASSIUM SALT ENRICHMENT - Belkin, P. A. (Vestnik Permskogo universiteta. Serii͡a︡ Geologii͡a, 2020)
Mining and processing of potassium salts in humide regions is inevitably connected with the disturbance of natural hydrochemical conditions. In order to describe the chemical composition of groundwater discharged in the immediate vicinity of potash waste storage facilities, spring flow studies were conducted, including sampling and analysis of the macro- and micro-component composition of eight springs over the period 2016-2018. A general description of the chemical composition of spring runoff waters is given, and correlations between the content of various components of their composition are studied. The obtained results make it possible to identify a number of chemicals that determine the technogenic transformation of the chemical composition of groundwater near potash waste storage facilities.